Modeling and control of a novel pneumatic two-stage piezoelectric-actuated valve. (May 2021) - Glück, Tobias; Büchl, Dominik; Krämer, Christian; Pfeffer, Andreas; Risle, Andreas; Hägele, Lena; Kugi, Andreas
Abstract: In manufacturing automation, there is a strong need for highly integrated intelligent components and subsystems. In this context, a novel two-stage pneumatic piezoelectric-actuated valve has recently been developed. It covers a wide range of pneumatic products and functions in one compact component and enables flexible and adaptive plant operation. The valve consists of four poppet main-stage valves that are driven by piezoelectrically actuated pre-stage valves and includes pressure sensors as well as a powerful computational unit. This work presents the systematic development of a model-based position control algorithm including modeling, identification, and controller design. The control concept comprises a hysteresis compensation based on the Prandtl–Ishlinskii operator theory, a flatness-based feedforward controller, and a PI feedback controller with appropriate anti-windup measures. Measurement results from a test bench demonstrate the performance of the proposed concept.